The Role of Using the Management by Walking Around In Administrative Reform in Lattakia Directorate of Education (Journal of Hama University, 2021)
The aim of the research is to study the role of Management by walking around in administrative reform in Lattakia Directorate of Education, by studying the effect of roaming management dimensions represented in discovering facts, improving communication, motivation, and feedback. The researcher relied on the descriptive analytical approach as a general approach to research. Designing a questionnaire and distributing it to a random sample of 135 in the Directorate of Education and its educational complexes. 134 The researcher used the statistical program Spss in conducting the statistical description and testing hypotheses, the researcher found that there is a positive moral impact between each of the dimensions of management by roaming and administrative reform. The researcher recommended that the Directorate of Education in Lattakia Governorate should adopt the management method by roaming, as well as re-study the regulations and laws related to routine matters, and work to fully automate the work and provide a database for the directorate